2020
DOI: 10.5194/acp-20-1105-2020
|View full text |Cite
|
Sign up to set email alerts
|

Molecular composition and photochemical lifetimes of brown carbon chromophores in biomass burning organic aerosol

Abstract: Abstract. To better understand the effects of wildfires on air quality and climate, it is important to assess the occurrence of chromophoric compounds in smoke and characterize their optical properties. This study explores the molecular composition of light-absorbing organic aerosol, or brown carbon (BrC), sampled at the Missoula Fire Sciences laboratory as a part of the FIREX Fall 2016 lab intensive. A total of 12 biomass fuels from different plant types were tested, including gymnosperm (coniferous) and angi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
240
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(255 citation statements)
references
References 79 publications
11
240
4
Order By: Relevance
“…It is possible that solvent extraction alters the BrC absorptivity in some OA-composition-dependent manner, leading to an apparent time-dependent decay in the BrC absorption. Consistent with this suggestion, Fleming et al (2020) reported that (i) the total absorptivity lifetime of BB particles photolytically aged on a filter greatly exceeded those of individual chromophores (>10 days versus <2 days), and (ii) the apparent changes in total absorption depended on whether the absorption was measured for particles on the filter versus for solution extracts. Nonetheless, this suggestion remains speculative as direct, quantitative comparisons between BrC absorption measured for suspended particles https://doi.org/10.5194/acp-2020-137 Preprint.…”
Section: Comparison With Ambient Observationsmentioning
confidence: 61%
See 1 more Smart Citation
“…It is possible that solvent extraction alters the BrC absorptivity in some OA-composition-dependent manner, leading to an apparent time-dependent decay in the BrC absorption. Consistent with this suggestion, Fleming et al (2020) reported that (i) the total absorptivity lifetime of BB particles photolytically aged on a filter greatly exceeded those of individual chromophores (>10 days versus <2 days), and (ii) the apparent changes in total absorption depended on whether the absorption was measured for particles on the filter versus for solution extracts. Nonetheless, this suggestion remains speculative as direct, quantitative comparisons between BrC absorption measured for suspended particles https://doi.org/10.5194/acp-2020-137 Preprint.…”
Section: Comparison With Ambient Observationsmentioning
confidence: 61%
“…) Lee et al (2014). photolytically aged water-soluble extracts of secondary BrC produced from photooxidation of naphthalene and observed a continuous decrease in the absorptivity, but again with a time constant that was likely too long to have influenced our experiments Fleming et al (2020). photolytically aged particles from 12 of the FIREX burns that were collected on Teflon filters.…”
mentioning
confidence: 81%
“…In these studies, the importance of nitrated and aromatic aerosol components for near UV light absorption has been highlighted. Several classes and subclasses of BrC chromophores have been identified, including nitroaromatics, polycyclic aromatic hydrocarbon (PAHs) and their derivatives, and lignin-derived products (Fleming et al, 2018(Fleming et al, , 2020Lin et al, 2018). Nitroaromatic compounds especially nitrophenols and nitrocatechols have been recognized as the prominent classes of BrC compounds, especially in biomass burning source samples and biomass burning influenced ambient aerosol and cloud water samples.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Saturno et al (2018b) have shown that the brown carbon (BrC) contribution to total absorption becomes increasingly important towards the end of the dry season. This is a further indication of the predominance of regional fires towards the later BB season, given that BrC is quickly photodegraded in the atmosphere after emission, with a typical lifetime of a few days to weeks (Fleming et al, 2020;Wong et al, 2019), comparable to the transport times of African BB emissions across the Atlantic.…”
Section: Estimated Relevance Of the Pollution Layer For Central Amazomentioning
confidence: 91%
“…During their typical atmospheric lifetime of several days, BC particles undergo photochemical aging, creating internally mixed BC aerosols via the condensation of low and semi-volatile compounds, coagulation, and cloud processing (Bond et al, 2013;Cubison et al, 2011;Konovalov et al, 2017Konovalov et al, , 2019Schwarz et al, 2008;Willis et al, 2016). The formation of non-absorbing or semi-transparent coatings on the BC cores changes the particles' optical properties (Fuller et al, 1999;Moffet and Prather, 2009;Pokhrel et al, 2017;Schnaiter, 2005;Zhang et al, 2015) as well as their ability to act as cloud condensation nuclei (CCN) (Laborde et al, 2013;Liu et al, 2017;Tritscher et al, 2011), which influences their atmospheric transport and lifetime.…”
Section: Introductionmentioning
confidence: 99%